What moves markets? - Mark Kerssenfischer; Maik Schmeling (Deutsche Bundesbank, 2022)
What share of asset price movements is driven by news? We build a large, time-stamped event database covering scheduled macro news as well as unscheduled events. We find that news account for about 50% of all bond and stock price movements in the United States and euro area since 2002, suggesting that a much larger share of return variation can be traced back to observable news than previously thought. Moreover, we provide stylized facts about the type of news that matter most for asset prices, the persistence of news effects, and spillover effects between the US and euro area.
Keywords: E43; E44; G12; G14; 330; Macro news; Asset prices; High-Frequency Identification; Event Database